Adsorption of Heavy Metals Fe and Mn in Acid Mine Drainage from Coal Mining Waste Using Calcium Oxide and Fly Ash - Hendra Pratama; Edy Nursanto; Rika Ernawati; Muhammad Giatman (Universitas Negeri Padang, 2022)
Acid mine drainage for Fe and Mn metals have a negative impact on the environment. This study studies the use of calcium oxide and fly ash as adsorbents, used to absorb Fe and Mn metals contained in acid mine drainage. This study aims to analyze the effectiveness of Calcium Oxide and fly ash as adsorbents, that an adsorbent of Fe and Mn metals in acid mine drainage. The method used is experimental with a laboratory scale, the test is carried out by adsorption using a batch system. Magnetic stirrer is used as a stirring medium in the adsorption process. Calcium oxide with various doses (0.1; 0.2; 0.3 grams) and fly ash with various doses (10; 14; 17 grams) were mixed with 250 ml acid mine drainage, then stirred at a speed of 150 rpm and (30; 60; 90 minutes) stirring time. The characterization of the adsorbent was carried out by SEM testing. The results show that fly ash adsorbent has a better adsorption effectiveness than calcium oxide. The effectiveness of Fe is 85.35% and Mn 78.14%. While calcium oxide has the effectiveness of Fe 72.91% and Mn 61.81%. SEM testing of holes that increase and enlarge after adsorption, as well as the filling of the cavity by the material indicates the success of the adsorption process.